Lift high the cross : where white supremacy and the Christian right converge - Burlein, Ann, 1963- (e-Duke books scholarly collection., 2002)
Explores the links between white supremacist organizations and groups representing the religious right, specifically in Colorado, home of the most well known of these organziations, Christian Identity and Focus in the Family.